EDUKASI KEGAWATDARURATAN HIPERTENSI DALAM MENINGKATKAN PENGETAHUAN LANSIA DENGAN HIPERTENSI - Sari Wijayaningsih, Kartika; Mutmainnah, Amriati; Mina La Isa, Wa; Ernawati, Ernawati; Mato, Rusni; Darwis, Darwis; Muzakkir, Muzakkir; Indrayani, Ferna (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Hypertension is a condition in which blood vessels have high blood pressure (systolic blood pressure ?140 mmHg or diastolic blood pressure ? 90 mmHg). This community service aims to invite the public to understand the emergency management of the elderly with hypertension. This community service was carried out on 30 hypertension patients. This activity includes; blood pressure checks and education on emergency management of the elderly with hypertension. The knowledge evaluation instrument used a hypertension knowledge questionnaire and blood pressure assessment using a sphygmomanometer. The provision of emergency education for the elderly with hypertension increased the knowledge score, the score before 42 and the score after 83 so that the post-test score increased by 98% from the pre-test score. The results of blood pressure examination for the elderly with a TD of > 140/90 mmHg were 21 people (70%) and the elderly with a TD of < 140/90 mmHg were 9 people (30%). Providing emergency education for the elderly with hypertension can increase the knowledge of the elderly related to hypertension so that the quality of life is maintained.